2020
DOI: 10.1186/s41182-020-00216-9
|View full text |Cite
|
Sign up to set email alerts
|

Skin disorders among children living in orphanage centres in Dar es Salaam, Tanzania

Abstract: Background: Skin conditions contribute significantly to the global burden of diseases and are among the leading causes of non-fatal disease burden. Children living in orphanage centres are vulnerable to several conditions including dermatological disorders, and there is limited data on the burden of these conditions among orphans in Tanzania. This study was carried out to determine the pattern of dermatological conditions and contributing factors among orphans in Dar es Salaam, Tanzania. Methodology: A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Tinea capitis, also known as scalp ringworm, is a highly contagious superficial fungal infection of the scalp and its associated hair follicles, occurring predominantly in children under 12 years of age 1,2 . Tinea capitis occurrence is not recorded by global or public health agencies; hence, the true burden is unknown 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tinea capitis, also known as scalp ringworm, is a highly contagious superficial fungal infection of the scalp and its associated hair follicles, occurring predominantly in children under 12 years of age 1,2 . Tinea capitis occurrence is not recorded by global or public health agencies; hence, the true burden is unknown 3 …”
Section: Introductionmentioning
confidence: 99%
“…Tinea capitis, also known as scalp ringworm, is a highly contagious superficial fungal infection of the scalp and its associated hair follicles, occurring predominantly in children under 12 years of age. 1,2 Tinea capitis occurrence is not recorded by global or public health agencies; hence, the true burden is unknown. 3 Majority of the cases reported are of children, and the mean age of onset is in patients aged between 3 and 7 years living in Africa or of sub-Saharan African descent living abroad.…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity profiling of various diseases in orphanages has been done in various parts of India and at the world level but a scientific structured study regarding the pattern and prevalence of dermatoses in child orphanages has never been done before in India. [ 1 4 5 6 7 ] All the above-mentioned studies have been done by the department of community medicine, pediatrics, and nursing health and none has been done by dermatologists which is required to make a specific diagnosis about dermatological problems. Also, they described diseases in general terms like skin rashes without any specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies done in orphanages globally and all over India frequently have reported superficial fungal and bacterial infections like dermatophytoses and pyodermas implicating poor level of hygiene and low socioeconomic status. [ 7 ] Similarly, a school study done by Dogra et al . [ 9 ] in Chandigarh (urban) also showed 64.4% of pyodermas and 25.4% of fungal infections which is in contrast to our study.…”
Section: Description Of the Dermatosesmentioning
confidence: 96%
“…A research study found that 35.5% of children face skin problems, 28.3% dental problems, 12.9% scalp problems, 11.6% ear problems, 5.7% upper respiratory problems, 3.9% eye problems, and 2.3% face other medical problems. Orphans, who stay in orphanages, have more medical problems as compared to those who live for limited time (Reddy & Ramya , 2017;Amiri, Furia, & Bakari, 2020). Many orphanages are un-organized in the context of staff (Browne, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%